Design and Implementation of A Single-Stage Full-Bridge DC/DC Converter with ZVS Mode - Diker, A.; Korkmaz, D.; Alcin, O. F.; Budak, U.; Gedikpinar, M. (Springer International Publishing Ag, 2014)
In this paper, a single-stage full-bridge converter with auxiliary circuit elements which allow its main power circuit switches to operate with ZVS mode is presented. By creating dead time between power switches and working across, high frequencies which are the basis of the soft-switching are reached. Thus, more uniform output of system is obtained. In addition, it is observed that output rectifier diodes are exposed to parasitic oscillations. Experimental results obtained from the prototype with DC 180V input voltage, DC 45V output voltage and 50kHz operation frequency are illustrated in the paper.
10th International Conference on Mechatronics -- OCT 07-09, 2013 -- Brno, CZECH REPUBLIC